GAYA BAHASA PERBANDINGAN DALAM NOVEL MARYAM KARYA OKKY MADASARI - Halfian, Wa Ode; Elfinawati, Elfinawati; Masri, Fina Amalia (Seshiski: Southeast Journal of Language and Literary Studies, 2023)
This study discusses comparative language style in the novel Maryam by Okky Madasari. The problem in this study is what kind of comparative language is found in the novel Maryam by Okky Madasari. The purpose of this study is to describe the style of comparative language in the novel Maryam by Okky Madasari. This research includes library research. The data and data sources in this study are words, phrases or sentences that contain comparative language styles contained in the novel Maryam by Okky Madasari, which consists of 275 pages published in April 2012 by PT Gramedia Pustaka Utama, Jakarta. This study found that; there 37 data, which indicated; (a) hyperbole 7 data, (b) metonomia (1) data, (c) personification 5 data, (d) parable 2 data, (e) metaphor 2 data, (f) allegory 1 data, (g) synecdoche 4 data, (h) allusion 2 data, (i) simile 3 data, (j) association 2 data, (k) euphemism 8 data.